The Role of Leadership Style, Motivation, and Discipline in Employee Performance at BKPSDM of Kepulauan Selayar Regency - Chalid, Lukman; Rahayu, Sri Annisa; Kamase, Jeni (Jurnal Manajemen Bisnis, 2024)
This research was conducted with the aim: (1) To Analyse and Explain the Effect of Leadership Style on Employee Performance at the Personnel and Human Resources Development Agency (BKPSDM) of Selayar Islands Regency, (2) To Analyse and Explain the Effect of Motivation on Employee Performance at the Personnel and Human Resources Development Agency (BKPSDM) of Selayar Islands Regency and (3) To Analyse and Explain the Effect of Discipline on Employee Performance at the Personnel and Human Resources Development Agency (BKPSDM) of Selayar Islands Regency. The research methods used in this research are Descriptive Analysis, Multiple Linear Regression Analysis, Instrument Test and Hypothesis Test with a sample size of 66 respondents. Based on the results of multiple linear regression analysis, the results showed that (1) Leadership style has a negative and insignificant effect on the performance of BKPSDM Selayar Islands Regency, (2) Motivation has a positive and significant effect on the performance of BKPSDM Selayar Islands Regency and (3) Discipline has a positive and significant effect on the performance of BKPSDM Selayar Islands Regency.